Decreasing the Presentation Speed of Animated Soccer Scenes Does Not Always Lead to Better Learning Outcomes in Young Players. Issue 8 (8th May 2020) - Rekik, Ghazi; Belkhir, Yosra; Mnif, Maha; Masmoudi, Liwa; Jarraya, Mohamed
ABSTRACT: Under what conditions, the use of design techniques improves learning from animations? The present experiment examined the effect of content complexity on learning from animated soccer scenes presented either at normal or low speeds ( i.e ., 0.5 and 1.0 times normal speed). One hundred young soccer players (Mage = 13.12 years, SD = 0.47) were randomly assigned to four experimental conditions and invited to rate their perceived mental effort and perform a comprehension test, immediately after the learning phase. Data analyses revealed that while the decrease of presentation speed has no advantages when learning low-complexity content, players profited more from the low than the normal presentation speed (in terms of mental effort and comprehension performance) when learning high-complexity content. The findings suggested that the decrease of presentation speed is particularly effective with the increase in the complexity of soccer scenes.